The Dual Role of Antimicrobial Peptides in Autoimmunity - Liang, Wenjie; Diana, Julien (Frontiers in Immunology, 2020)
Autoimmune diseases (AiDs) are characterized by the destruction of host tissues by the host immune system. The etiology of AiDs is complex with the implication of multiple genetic defect and various environmental factors (pathogens, antibiotic use, pollutants, stress, diet...). The interaction between these two compartments result in the rupture of tolerance against self-antigen and the unwanted activation of the immune system. Thanks to animal models, the immunopathology of many AiDs is well-described with the implication of both the innate and adaptive immune systems. This progress towars the understanding of AiDs led to several therapies tested in patients. However, the results from these clinical trials have not been satisfactory, from reversing the course of AiDs to preventing them. The need for a cure has prompted many investigators to explore alternative aspects in the immunopathology of these diseases. Among these new aspects, the role of antimicrobial host defense peptides (AMPs) is growing. Indeed, beyond their antimicrobial activity, AMPs are potent immunomodulatory molecules and consequently are implicated in the development of numerous AiDs. Importantly, according to the disease considered, AMPs appears to play dual role in autoimmunity with either anti- and pro-inflammatory abilities. Here, we aim to summarize the current knowledge about the role of AMPs in the development of AiDs and we attempt to provide some hypotheses explaining their dual role. Definitely, a complete understanding of this aspect is mandatory before the design of AMPs-based therapies against AiDs.